Data from: Soil biota and chemical interactions promote co-existence in co-evolved grassland communities - Semchenko, Marina; Nettan, Siim; Sepp, Anette; Zhang, Qiaoying; Abakumova, Maria; Davison, John; Kalamees, Rein; Lepik, Anu; Püssa, Kersti; Saar, Sirgi; Saarma, Merilin; Thetloff, Marge; et al. (Dryad, 2019)
1. Plant populations can exhibit local adaptation to their abiotic
environment, such as climate and soil properties, as well as biotic
components such as the chemical signatures of dominant plant species and
mutualistic and pathogenic microbial populations. While patterns of local
adaptation in individual species are widely recorded, the importance of
microevolutionary processes for plant community assembly and function is
poorly understood. 2. Here we examined how a history of long-term
co-existence, and thus potential for local co-adaptation, influenced the
process of plant community assembly. Soil inocula and seeds of eight plant
species were collected from three calcareous grasslands with a long
history of grazing within a single geographical region. Mesocosm
communities were established using local genotypes from a single site or
an artificial mixture of genotypes from two different sites. To
investigate the role of root exudates and local (“home”) and non-local
(“away”) soil biota as mediators of plant species co-existence, the
population origin treatment was combined with the addition of activated
carbon, which is known to adsorb exudates from soil, and sterilisation of
soil inocula. Individual-, species- and mesocosm-level responses were
measured over the course of three growing seasons. 3. We found that root
exudates promoted seedling survival, species co-existence and productivity
in assemblages of genotypes originating from the same community but had a
weak impact in mixed, novel communities. Soil biota promoted the growth of
subordinate forbs and restrained the growth of dominant graminoids,
particularly in communities composed of local genotypes. The effects of
population origin were significant in the first two years of the
experiment but were not detectable in the third year when interbreeding
and new seedling establishment took place. Plant genotypes coupled with
“home” microbial inoculum experienced a stronger reduction in growth
compared with genotypes exposed to “away” inoculum, indicating that plants
experienced home-field disadvantage in interactions with soil biota. 4.
Synthesis. Our study demonstrates that the mechanisms of initial grassland
community assembly depend on community history, with belowground chemical
interactions and plant interactions with soil biota becoming stronger
drivers of dynamics in established and potentially co-evolved communities.
Semchenko_et_al_2019_JEcol_dataData were collected over three years from a
common garden, mesocosm experiment, maintained in Tartu, Estonia. Pot –
pot ID; Community_type – local or mixed plant community; Activated_carbon
– with or without activated carbon addition; Inoculation - sterilised or
non-sterilised soil inoculum; Population_origin – genotype origin (site A,
B or C); Community_composition – origin of plant community (site A, B or C
for local communities or AB, AC, CB for mixed communities); Species_ID –
species ID; Shoot_mass_Year1_g - individual dry shoot mass at the end of
the first growth season; State_Year1 – individual survival at the end of
the first growth season; Shoot_mass_Year2_g - individual dry shoot mass at
the end of the second growth season; State_Year2 - individual survival at
the end of the second growth season; Inoculum_origin – soil inoculum
origin (site A, B or C); Inoculum_type – inoculum relationship to plant
individual (home or away); Shoot_mass_Year3_g - species dry shoot mass at
the end of the third growth season; State_Year3 - species survival at the
end of the third growth season; Root_diameter_mm – root mean diameter from
mixed community samples at the end of the first growth season; Root_mass_g
– root dry mass at the end of the first growth season (sum of two soil
cores); Specific_root_length_cm_mg – specific root length from mixed
community samples at the end of the first growth
season.Semchenko_et_al_2019_data_table.xlsx
Keywords: Hypericum perforatum; Inula salicina; Carex flacca; 2012-2014; eco-evolutionary dynamics; Pilosella officinarum; Leontodon hispidus; Root exudates; plant community assembly; belowground interactions; Campanula rotundifolia; Festuca ovina; Galium verum; community evolution; grassland restoration; soil microbial interactions